Contextual Verbal Creativity Test (CVCT): A New Tool For Understanding Verbal Creativity Among Students Of University X - Gunjaya, Renata V.; Ang, Cecilia; Sania, Sania; Suyasa, Tommy (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
Creativity is the intellectual ability to produce new ideas that are useful in everyday life. Creativity consists of musical, kinesthetic, organizational, figural and verbal creativity. Among these types, verbal creativity is the most relevant type of creativity and is widely used in everyday life. In Indonesia, several measuring instruments have been developed to measure verbal creativity. However, some measurement tools that have been developed still have not considered context. Recognizing the importance of context in making creativity more relevant and beneficial, research was conducted to develop a contextual computer-based verbal creativity measurement tool. This research aims to obtain psychometric information from a contextual verbal creativity measuring tool (Contextual Verbal Creativity Test [CVCT]), which was developed to improve previous verbal creativity measuring tools. Researchers compiled a CVCT consisting of twenty adjectives. Testing of the measuring instrument was carried out on 100 University X students. CVCT measures four aspects: fluency, flexibility, originality and elaboration. Findings from this research are: (a) internal consistency reliability of CVCT; (b) descriptive statistic of CVCT measurement; (c) CVCT norms for each aspect; (d) criterion validity of CVCT on academic achievement; and (e) construct validity of CVCT based on gender.